Análise da influência da gestão de projetos e do lean thinking no desempenho das empresas da construção civil - Scheleider, Avner Augusto (2024)
With the high competitiveness in the construction industry, companies seek management models that strengthen their performance. Project management plays a significant role in the success of construction sector enterprises, making projects more efficient or even feasible. The Lean Thinking approach complements this scenario, recognized for its ability to enhance companies’ competitiveness. Combining these approaches raises a central point of interest: evaluating the effects of the relationship between these theories and their impact on companies’ operational and outcome performance. Thus, this research aims to analyze the relationship between project management knowledge areas when aligned with Lean Office practices on the performance of construction sector companies. To achieve this goal, an applied, descriptive, and quantitative research was conducted, fundamentally based on the survey method for systematically collecting primary data from a population of construction companies of various sizes. These data underwent statistical analysis for descriptive and correlational evaluation. The results, supported by statistical evidence, identified the correlation and relevance of project management and Lean Thinking approaches in relation to project team performance and overall company performance. These findings may guide managers in better allocating investments and efforts to enhance company competitiveness in areas identified as most relevant.